Cooling Machines and Coefficient of Performance Calculations in Refrigeration Systems - Safitri, Puspa Dinda; A. Hidayat; H A Geralfine; D.Y Nugraha; N. A Tasya; F.H.R Nurrokhim; I.A. Fayrezzi; I. Habibullah; W. Saputro; R.D. Issafira (BIOMEJ, 2024)
A cooling machine is an energy conversion machine that is used to transfer heat from a high temperature hot reservoir to a higher temperature hot reservoir by adding work from outside. In clear terms, a cooling machine is equipment used in the process of cooling a material (fluid) so that it reaches the desired temperature and humidity, by absorbing heat from the material (fluid) that will be conditioned, or in other words absorbing heat (heat) from a cold reservoir. and given to the hot reservoir. The method used in this experiment is a quantitative method where we collect data and then process the data to get the Coefficient of Performance (COP) value. the average temperature in the 5th minute was 24.7 ˚C, in the 10th minute it was 22.34 ˚C, in the 15th minute it was 21.66 ˚C, in the 20th minute it was 21.42 ˚C, at the 25th minute it was 21.32 ˚C, and at the 30th minute it was 21.2 ˚C. COPmax data above the 5th minute to the 10th minute there is a temperature decrease of 5.74%, where the temperature decrease is the highest temperature speed decrease compared to other minutes because the series of tools working in the first 5 minutes has a temperature decrease speed of the minute temperature. 5th minute of 24.7 ˚C towards the 10th minute average temperature of 22.34 ˚C. Meanwhile, the decrease in temperature from the 10th minute to the 15th minute was 2.95%. From the 15th minute to the 20th minute temperature, there was a decrease of 2.82%. For the temperature from the 20th minute to the 25th minute, the temperature decreased by 2.77%. Then from the 25th minute to the 30th minute, the temperature decreased by 2.71%. COPactual data calculations also showed a decrease where in the 5th minute it was 0.75%, in the 10th minute 0.33%, in the 15th minute 0.09%, in the 20th minute 0.03%, while in the 25th and 30th minutes the temperature starts constant with a decrease of 0.01%